(untitled) (Pursuits: A Journal of English Studies, 2025)
This article analyzes those verses of the Bhagavad Gita that deals with some of the major vedic concepts. It aims to highlight the connection between the Gita and the ancient Aryan texts — the Vedas. The article addresses the research problems concerning to the linkages between the Gita and the Vedas and the contradictory aspects of the Gita’s interpretations of the major vedic concepts. The Bhagavad Gita and the Vedas are considered the sacred Hindu religious texts but they were not written at the same time. The Vedas were written centuries earlier than the Bhagavad Gita and the Gita, consequently, borrows some concepts from the Vedas. The article examines the verses of the Gita by applying the theoretical framework of historical materialism. Its application to the text reveals that the Gita gives high priority to some of the vedic concepts interpreted by the Brāhmaṇic ideology known as Pūrvamīmāṁsā in some verses, but some other verses minimizes these concepts highlighting the Upanisadic concepts developed later. The Gita also borrows some concepts from the Hindu’s sacred texts the Upanisads, compiled later than the Vedas and this makes the Gita self- contradictory while dealing with the vedic concepts. This exhibits the incompatibility of the Gita in its interpretations to the major vedic ideals.